An exploration of the factors that influence nurse practitioner transition in Australia: A story of turmoil, tenacity, and triumph. Issue 3 (10th November 2016) - MacLellan, Lorna; Higgins, Isabel; Levett‐Jones, Tracy
Abstract: Background and purpose: Nurse practitioner (NP) legislation was introduced in Australia in 1998 with the first NPs endorsed 2 years later. Although the number of NPs has slowly increased, they still face significant challenges adjusting to their new role. The aim of this study was to explore the factors that influence the experience of new NPs. Methods: Ten newly appointed NPs were interviewed three to four times over a 12‐month period. Using a summative content analysis, data were reduced to four key factors that influence the experience of role transition: personal, intraprofessional, interprofessional, and organizational. Conclusions: The findings illustrate that for many participants, transition was a time of turmoil and a great deal of tenacity was required to navigate the journey. However, despite the challenges, some participants were triumphant and able to forge a successful role for themselves. Implications for practice: This study highlights the need for the nursing profession to support new NPs. It also demonstrates that the provision of structured orientation programs is needed to facilitate effective transition to these complex and challenging roles. Clarity of expectations and a gradual increase in responsibilities are likely to optimize adjustment to the NP role.